Trilha das estrelas: um jogo facilitador no processo de ensino-aprendizagem - Secchin, Gêssica Clevelares (2023)
Understanding that the teaching-learning process in relation to the discipline of Physics is a challenge for the present day, this work proposes a didactic sequence with an approach to teaching Astronomy using a didactic game with emphasis on an interdisciplinary activity with the Chemical. The methodology is structured on the qualitative analysis of the data through the construction and application of the game "Trilha das Estrelas", and research, of a descriptive and bibliographic nature, considering the transformation and production of knowledge with students of a 2nd grade class of high school in a public school in the city of Cachoeiro de ItapemirimES. From the development of activities and grounded in Vygotsky's Sociointeractionist Theory, where the interrelationship between students and professor, allows an exchange of significant knowledge and enriching experiences for learning, the importance of activities that enable the construction of new knowledge, as the main result, from a collective and cooperative process, reinforcing the development of interactions between knowledge agents, contributing to the importance of creating circumstances that promote the learning process, which allows a better meaning of scientific concepts.